Resistance of Anopheles stephensi to selected insecticides used for indoor residual spraying and long-lasting insecticidal nets in Ethiopia - Abebe Teshome; Berhanu Erko; Lemu Golassa; Gedeon Yohannes; Seth R. Irish; Sarah Zohdy; Melissa Yoshimizu; Sisay Dugassa (Malaria Journal, 2023)
Abstract Background Malaria, transmitted by the bite of infective female Anopheles mosquitoes, remains a global public health problem. The presence of invasive Anopheles stephensi, capable of transmitting Plasmodium vivax and Plasmodium falciparum, was first reported in Ethiopia in 2016. The ecology of this mosquito species differs from that of Anopheles arabiensis, the primary malaria vector in Ethiopia. This study aimed to evaluate the efficacy of selected insecticides, which are used in indoor residual spraying (IRS) and selected long-lasting insecticidal nets (LLINs) for malaria vector control against adult An. stephensi. Methods Anopheles stephensi mosquitoes were collected as larvae and pupae from Awash Subah Kilo Town and Haro Adi village, Ethiopia. Adult female An. stephensi, reared from larvae and pupae collected from the field, aged 3–5 days were exposed to impregnated papers of IRS insecticides (propoxur 0.1%, bendiocarb 0.1%, pirimiphos-methyl 0.25%), and insecticides used in LLINs (alpha-cypermethrin 0.05%, deltamethrin 0.05% and permethrin 0.75%), using diagnostic doses and WHO test tubes in a bio-secure insectary at Aklilu Lemma Institute of Pathobiology, Addis Ababa University. For each test and control tube, batches of 25 female An. stephensi were used to test each insecticide used in IRS. Additionally, cone bioassay tests were conducted to expose An. stephensi from the reared population to four brands of LLINs, MAGNet™ (alpha-cypermethrin), PermaNet® 2.0 (deltamethrin), DuraNet© (alpha-cypermethrin) and SafeNet® (alpha-cypermethrin). A batch of ten sugar-fed female mosquitoes aged 2–5 days was exposed to samples taken from five positions/sides of a net. The data from all replicates were pooled and descriptive statistics were used to describe features of the data. Results All An. stephensi collected from Awash Subah Kilo Town and Haro Adi village (around Metehara) were resistant to all tested insecticides used in both IRS and LLINs. Of the tested LLINs, only MAGNet™ (alpha-cypermethrin active ingredient) caused 100% knockdown and mortality to An. stephensi at 60 min and 24 h post exposure, while all other net brands caused mortality below the WHO cut-off points (< 90%). All these nets, except SafeNet®, were collected during LLIN distribution for community members through the National Malaria Programme, in December 2020. Conclusions Anopheles stephensi is resistant to all tested insecticides used in IRS and in the tested LLIN brands did not cause mosquito mortality as expected, except MAGNet. This suggests that control of this invasive vector using existing adult malaria vector control methods will likely be inadequate and that alternative strategies may be necessary.